Climate change mitigation scenarios and policies and measures: the case of Kazakhstan. (2nd April 2016) - Kerimray, Aiymgul; Baigarin, Kanat; De Miglio, Rocco; Tosato, Giancarlo
Abstract : This article illustrates the main difficulties encountered in the preparation of GHG emission projections and climate change mitigation policies and measures (P&M) for Kazakhstan. Difficulties in representing the system with an economic model have been overcome by representing the energy system with a technical-economic growth model (MARKAL-TIMES) based on the stock of existing plants, transformation processes, and end-use devices. GHG emission scenarios depend mainly on the pace of transition in Kazakhstan from a planned economy to a market economy. Three scenarios are portrayed: an incomplete transition, a fast and successful one, and even more advanced participation in global climate change mitigation, including participation in some emission trading schemes. If the transition to a market economy is completed by 2020, P&M already adopted may reduce emissions of CO2 from combustion by about 85 MtCO2 by 2030 – 17% of the emissions in the baseline (WOM) scenario. One-third of these reductions are likely to be obtained from the demand sectors, and two-thirds from the supply sectors. If every tonne of CO2 not emitted is valued up to US10 in 2020 and 20 in 2030, additional P&M may further reduce emissions by 110 MtCO2 by 2030.